STRATEGI PERENCANAAN PAJAK DAN IMPLIKASINYA TERHADAP MANAJEMEN LABA PADA SEKTOR PERBANKAN DI INDONESIA - Wirda Muhibbatul Lubabah (CV. Adiba Aisha Amira, 2025)
This study aims to examine the effect of tax planning on earnings management in the banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. In a high-pressure business environment, tax planning strategies are often employed by management to optimize tax burdens while also influencing reported earnings. This research uses a quantitative approach with multiple linear regression analysis. The results indicate that tax planning has a positive and significant effect on earnings management. These findings support agency theory, which posits that managers, as agents, have incentives to manage earnings to meet specific targets or maintain reputations. Therefore, tax strategies should be carried out ethically and transparently to avoid misleading investors or regulators.